Pandora's flying box - Borrelia burgdorferi sensu lato prevalence in Ixodes species from birds throughout Europe - Norte, A. C. (2018)
Birds are important hosts for ticks and may act as reservoirs for several zoonotic pathogens. Because of their high mobility, especially of the long distance migratory species, they can act as dispersers for ticks and pathogens, ultimately affecting their distribution and phylogeography.